2015
DOI: 10.1177/1541931215591063
|View full text |Cite
|
Sign up to set email alerts
|

UX Day Design Challenge

Abstract: Hackathons have become a popular method for group design ideation and conceptual development for practical design challenges in a variety of technology domains. Perhaps the most common is software development and a common application is for social entrepreneurship, as a way to assist worthy causes in a short amount of time and at low cost. Companies also use hackathons as a source of new ideas for challenging design objectives or to audition potential employees and contractors. One of the major benefits of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Hackathons have only recently come into research focus (Trainer et al 2016). Studies have investigated the individual experiences of participants (Olesen, Hansen & Halskov 2018), the effect of expertise diversity in hackathon teams (Legardeur et al 2020) and the use of hackathons to solve problems (Artiles & LeVine 2015; Lewis et al 2015; Uffreduzzi 2017; Kos 2019), teach design (Fowler 2016; Nandi & Mandernach 2016; Page et al 2016; Gama et al 2019) and facilitate a design process (Artiles & Wallace 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hackathons have only recently come into research focus (Trainer et al 2016). Studies have investigated the individual experiences of participants (Olesen, Hansen & Halskov 2018), the effect of expertise diversity in hackathon teams (Legardeur et al 2020) and the use of hackathons to solve problems (Artiles & LeVine 2015; Lewis et al 2015; Uffreduzzi 2017; Kos 2019), teach design (Fowler 2016; Nandi & Mandernach 2016; Page et al 2016; Gama et al 2019) and facilitate a design process (Artiles & Wallace 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A literature review by Flus & Hurst (2021a) encompassing 39 studies on design research at hackathons revealed various themes in educational hackathon research, including the experiences of participants (Olesen, Hansen, & Halskov 2018) and the impact of interdisciplinary teams on team performance (Legardeur et al 2020). Furthermore, numerous papers have shared qualitative insights and anecdotes from hackathons as design educational formats (Artiles & Wallace 2013; Artiles & LeVine 2015; Lewis et al 2015; Fowler 2016; Nandi & Mandernach 2016; Page et al 2016; Gama et al 2018; Kos 2019). Remarkably, among the 39 papers examined, merely 10 employed quantitative methods, exposing a gap in the quantitative research of hackathons as educational formats.…”
Section: Introductionmentioning
confidence: 99%